Necessary defense and apprehension in the professor I. S. Tishkevich writings - Savenok, Anatoly L.; Bahur, Oleg I. (Journal of the Belarusian State University. Law, 2019)
The article is devoted to the study of the scientific creativity of professor I. S. Tishkevich in terms of the conditions and limits of causing harm in repelling a socially dangerous assault or detention of a criminal, as well as analyzing the composition of crimes committed while exceeding the limits of the necessary defense. It is noted that the original theoretical constructions built on the basis of a huge practical material have not lost their relevance over the years, but, on the contrary, provide an opportunity to rethink the modern criminal-legal reality in a new way.